2021
DOI: 10.5498/wjp.v11.i11.1053
|View full text |Cite
|
Sign up to set email alerts
|

Phantom bite syndrome: Revelation from clinically focused review

Abstract: Phantom bite syndrome (PBS), also called occlusal dysesthesia, is characterized by persistent non-verifiable occlusal discrepancies. Such erroneous and unshakable belief of a “wrong bite” might impel patients to visit multiple dental clinics to meet their requirements to their satisfaction. Subsequently, it takes a toll on their quality of life causing, career disruption, financial loss and suicidal thoughts. In general, patients with PBS are quite rare but distinguishable if ever encountered. Since Marbach re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…These patients are at a risk of overtreatment due to their persistent complaint of abnormal occlusion and strong desire for dental procedures. 19 , 20 In fact, our findings showed that patients with PBS were often in the process of prosthetic rehabilitation with temporary crowns, and because temporary crowns were counted in the DT score, we speculated that the DT and DMFT scores might have been higher.…”
Section: Discussionmentioning
confidence: 80%
“…These patients are at a risk of overtreatment due to their persistent complaint of abnormal occlusion and strong desire for dental procedures. 19 , 20 In fact, our findings showed that patients with PBS were often in the process of prosthetic rehabilitation with temporary crowns, and because temporary crowns were counted in the DT score, we speculated that the DT and DMFT scores might have been higher.…”
Section: Discussionmentioning
confidence: 80%
“…Estos matices en la evidencia resaltan la complejidad del tabaco como un factor de salud bucodental y la necesidad de una comprensión más matizada para abordar efectivamente este problema de salud pública, tal como se puede interpretar de estudios recientes. (10,11,12,13,14) A la luz de los hallazgos obtenidos en esta investigación, se proponen las siguientes recomendaciones para abordar las implicaciones en la salud bucodental relacionadas con el consumo de tabaco:…”
Section: Discussionunclassified